Oxidized cholesteryl ester induces exocytosis of dysfunctional lysosomes in lipidotic macrophages - Domingues, Neuza (2023)
Funding Information: This work was financially supported by FCT (Foundation for Science and Technology of the Portuguese Ministry of Science and Higher Education) through national funds and co‐funded by FEDER under the PT2020 Partnership (Ref. PTDC/MED‐PAT/29395/2017, 2022.01305.PTDC and 2022.03249.PTDC). The Coimbra Chemistry Center (CQC) is supported by the FCT through Project UID/QUI/00313/2019. MSCA‐RISE: “Genetic and Small Molecule Modifiers of Lysosomal Function” (LysoMod), financed by Horizon 2020. Ref 734825. Twinning on “Excel in Rare Diseases' Research: Focus on LYSOsomal Disorders and CILiopathies”, Ref (H2020‐TWINN‐2017: GA 81108). Neuza Domingues was a holder of PhD fellowship from the FCT (Ref. No: SFRH/BD/51877/2012), attributed by Inter‐University Doctoral Programme in Ageing and Chronic Disease (PhDOC). André R.A. Marques was funded by the FCT Stimulus of Scientific Employment Individual Support Call 2017 (CEECIND/01006/2017). Rosa Puertollano was funded by the NHLBI Division of Intramural Research (ZIA HL006151‐10). Publisher Copyright: © 2023 John Wiley & Sons A/S. Published by John Wiley & Sons Ltd.